Tectonics of the Isua supracrustal belt 1: P-T-X-d constraints of a poly-metamorphic terrane. Whole rock major elements chemistry from metamorphic rocks (IEDA: EarthChem Library)
This dataset presents major elements whole rock chemistry from amphibolites, meta-felsic volcanic and metasedimentary rocks from the Eoarchean Isua supracrustal belt. Samples were collected during a camping in the summer of 2017.